Effect of Melatonin on the Renin-Angiotensin-Aldosterone System in l-NAME-Induced Hypertension - Simko, Fedor; Baka, Tomáš; Krajcirovicova, Kristina; Repová, Kristína; Aziriova, Silvia; Zorad, Štefan; Poglitsch, Marko; Adamcova, Michaela; Reiter, Russel J; Paulis, Ludovit (Molecules, 2018)
The renin-angiotensin-aldosterone system (RAAS) is a dominant player in several cardiovascular pathologies. This study investigated whether alterations induced by l-NAME, (NLG)-nitro-l-arginine methyl ester, a nitric oxide synthase inhibitor, and the protective effect of melatonin are associated with changes in the RAAS. Four groups of 3-month-old male Wistar rats (n = 10) were treated as follows for four weeks: untreated controls, rats treated with melatonin (10 mg/kg/day), rats treated with l-NAME (40 mg/kg/day), and rats treated with l-NAME + melatonin. l-NAME administration led to hypertension and left ventricular (LV) fibrosis in terms of enhancement of soluble, insoluble and total collagen concentration and content. Melatonin reduced systolic blood pressure enhancement and lowered the concentration and content of insoluble and total collagen in the LV. The serum concentration of angiotensin (Ang) 1-8 (Ang II) and its downstream metabolites were reduced in the l-NAME group and remained unaltered by melatonin. The serum aldosterone level and its ratio to Ang II (AA2-ratio) were increased in the l-NAME group without being modified by melatonin. We conclude that l-NAME-hypertension is associated with reduced level of Ang II and its downstream metabolites and increased aldosterone concentration and AA2-ratio. Melatonin exerts its protective effect in l-NAME-induced hypertension without affecting RAAS.
Keywords: krevní tlak; krysa rodu Rattus; Animals; hypertenze; mužské pohlaví; zvířata; renin-angiotensin systém; Hypertension; Blood Pressure; NG-nitroargininmethylester; Male; NG-Nitroarginine Methyl Ester; Melatonin; Rats, Wistar; Rats; melatonin; Renin-Angiotensin System; potkani Wistar